Deceptive ambiguity by police and prosecutors - Shuy, Roger W. (Oxford studies in language and law, 2017)
Introduction -- Power, ambiguity, and deception -- Police interviewers use deceptive ambiguity -- Prosecutors use deceptive ambiguity -- Undercover agents use deceptive ambiguity -- Cooperating witnesses use deceptive ambiguity -- Complainants use deceptive ambiguity -- Deceptive ambiguity in the language elements -- The effects, frequency, and power of the government's uses of deceptive ambiguity in criminal investigations